DESIGN AND DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON CONTEXTUAL TEACHING LEARNING (CTL) IN THE SUBJECT OF EVALUATION AND SUPERVISION OF GUIDANCE AND COUNSELING - Munir, Abdul; Lubis, M. Rajab; Ginting, Rafael Lisinus (Journal of Community Research and Service, 2019)
The background of this study is based on the needs analysis of interactive media on Guidance and Counseling department in Universitas Negeri Medan which is equal to 98.1% of lecturers and students stating that they have not used interactive learning media in the classroom, 100% of lecturers andstudents stated that they need interactive media in the learning process and as many as 28% of lecturers and students recognize interactive media with macromedia flash and 72% of lecturers and students do not know the macromedia flash. The purpose of this study is to find out the needs and develop the initial product, carry out and know the expert and field testing, and carry out product effectiveness tests. The research method used is Research and Development method proposed by Borg and Gall, adapting theresearch procedure into three stages, namely: 1st stage introduction, 2nd stage product trial, and 3rd stage test thie effectiveness of the product. The average value of the experimental class pre-test is 52.20 with the highest value and the lowest value 37.5 and the standard deviation 8.09 while for the average post-test value is 85.15 with the highest value 100 and the lowest value 75, 00 and standard deviation of 6.30. The average value of the control class pre test is 51.62 with the highest value of 87.50 and thelowest value of 65.00 and the standard deviation of 10.28 whereas for the average post-test value is 76.91 with the highest value of 98 and the value lowest 75 and standard deviation 6.30. Keywords: Learning Media, Macromedia Flash, Evaluation and Supervision of Guidance andCounseling, Contextual Teaching Learning (CTL).